NOTCH 1 Mutation in a Patient with Spontaneous and Recurrent Dissections of Extracranial Arteries - Guevara, Carlos; Farias, Gonzalo; Bulatova, Kateryna; Alarcón, Pablo; Soruco, Wendy; Robles, Carlos; Morales, Marcelo (Frontiers in Neurology, 2017)
Dissections of extracranial arteries are estimated to account for only 2% of all ischemic strokes but for approximately 20% of strokes in patients younger than 45 years old.1 Most dissections of extracranial arteries involve some trauma stretch, mechanical stress or connective tissue abnormalities.1, 2 3 In the absence of these disorders, determining the etiology of recurrent extracranial dissections is quite challenging because the underlying nature of these cases is poorly understood. We report the case of a 44-year-old female with recurrent dissections of the vertebral and carotid arteries associated with a heterozygous mutation p.Pro2122Leu in the NOTCH 1 gene. Her mother with a thoracic aortic aneurysm was also positive for this variant.